2011
DOI: 10.7476/9788575413852
|View full text |Cite
|
Sign up to set email alerts
|

Amor e violência: um paradoxo das relações de namoro e do ‘ficar’ entre jovens brasileiros

Abstract: Gerar conhecimento estratégico sobre o tema da violência no namoro e no ‘ficar’ dos adolescentes brasileiros: este foi o objetivo de um estudo pioneiro realizado por pesquisadores de nove universidades públicas e da Fiocruz. O trabalho, que teve início em 2007, coletou, produziu e analisou dados quantitativos e qualitativos de âmbito nacional. O estudo foi realizado com cerca de 3.200 jovens, de 15 a 19 anos, matriculados em escolas públicas e particulares de dez cidades (Belo Horizonte, Brasília, Cuiabá, Flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
2
48

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 141 publications
12
54
2
48
Order By: Relevance
“…Although the studies adopted different methodologies, they reveal the magnitude of the phenomenon, corroborating the results of a study carried out in 10 Brazilian state capitals with 3,205 male and female adolescents (2) . The results indicated that 86.9% of the adolescents had already been victims of some type of violence, and 86.8% confirmed having committed some form of aggression during a rela- (29) .…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Although the studies adopted different methodologies, they reveal the magnitude of the phenomenon, corroborating the results of a study carried out in 10 Brazilian state capitals with 3,205 male and female adolescents (2) . The results indicated that 86.9% of the adolescents had already been victims of some type of violence, and 86.8% confirmed having committed some form of aggression during a rela- (29) .…”
Section: Discussionsupporting
confidence: 62%
“…The results revealed an 86.9% prevalence of victimization and 86.8% for perpetration of some form of aggression during relationships, with 76.6% of young men and women being both victims and offenders of various forms of aggression (2) . The study points to the need for adolescent dating violence prevention and intervention strategies, considering both the magnitude and the vulnerabilities determined by the experiences that mark this generation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A partir da conceituação de "violência no namoro", o trabalho dispõe-se a analisar pesquisas de abrangência nacional sobre violência contra mulheres e violência contra jovens (MAPA DA VIOLÊNCIA, 2015; MAPA DA VIOLÊNCIA, 2014; IPEA, 2014) a fim de identificar elementos que indiquem a relevância do fenômeno. Além disso, subsidia-se na pesquisa realizada entre 2007 e 2010 sobre as relações de namoro e do "ficar" entre jovens brasileiros (MINAYO, 2011), em que se investigou a condição juvenil no século XXI e a violência no contexto de relações amorosas e sexuais. Por fim, almeja analisar as diretrizes legais e políticas de enfrentamento à violência contra as mulheres e meninas na perspectiva educacional, a fim de vislum-brar as possibilidades da implementação de ações preventivas direcionadas à juventude.…”
Section: Desafios Para O Recorte Etário E Interseccional Na Implementunclassified